ECTOPIC PREGNANCY WITH TUBAL RUPTURE: AN ANALYSIS OF 80 CASES - Ashfaq, Sana; Sultan, Sadia; Aziz, Safia; Irfan, Syed Mohammed; Hasan, Miray; Siddique, Afshan (Journal of Ayub Medical College Abbottabad, 2017)
Background: Ectopic pregnancy (EP) is a major problem in obstetrics as there is evidence of increasing incidence throughout the world. It is an important cause of maternal morbidity and mortality. In Pakistan, the care seeking behaviour among female is limited that makes female vulnerable to die due to complication of ectopic pregnancy. The aim of this study is to determine the frequency of tubal rupture in ectopic pregnancy in Pakistani patients. Method: In this cross-sectional study data pertaining to age, gestational age, parity and duration of presenting symptoms were collected and analysed. Result: 80 patients were diagnosed to have ectopic pregnancy. The frequency of tubal rupture was 91.25%. It is encountered significantly more often in women with age of 26 years. More tubal rupture is found in patient with low parity, in which the frequency of tubal rupture is up to 100% and decrease up to 78.6% with increasing parity up to four. Furthermore, it is noted that increase in gestational age from 8 weeks to 10 weeks caused an increase in frequency of tubal rupture from 80 to 100% respectively. It is also noted that earlier the patient presents the lesser is the frequency of tubal rupture, as compared to late presentation beyond 3-4 days which make frequency up to 95%. Conclusion: Tubal rupture is still common cause of maternal morbidity and mortality, and is still a major challenge in gynaecological practice. Creating awareness amongst midwives and GPs regarding early diagnosis can contribute to decrease the mortality, morbidity and fertility loss related to EP. Keywords: Ectopic pregnancy; Tubal rupture; Ultrasonography; Laparotomy